2014
DOI: 10.1103/physreve.90.052132
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of work fluctuations by optimal control: An approach based on Jarzynski's equality

Abstract: Understanding and manipulating work fluctuations in microscale and nanoscale systems are of both fundamental and practical interest. For example, aspects of work fluctuations will be an important factor in designing nanoscale heat engines. In this work, an optimal control approach directly exploiting Jarzynski's equality is proposed to effectively suppress the fluctuations in the work statistics, for systems (initially at thermal equilibrium) subject to a work protocol but isolated from a bath during the proto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 44 publications
0
32
0
2
Order By: Relevance
“…Third, we have emphasized above that a quantum adiabatic process may be executed via a control field by taking advantage of STA [7,8,[22][23][24]. Consider, for example, one type of STA, which is also called counter-diabatic driving [22] or transitionless quantum driving [23].…”
Section: Principle Of Minimal Work Fluctuations: Quantum Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, we have emphasized above that a quantum adiabatic process may be executed via a control field by taking advantage of STA [7,8,[22][23][24]. Consider, for example, one type of STA, which is also called counter-diabatic driving [22] or transitionless quantum driving [23].…”
Section: Principle Of Minimal Work Fluctuations: Quantum Systemsmentioning
confidence: 99%
“…In our previous study [7] treating classical systems, a classical version of STA to realize classical shortcuts to adiabaticity [8] and a classical OCT were considered to suppression classical work fluctuations. It was found that the performance of OCT, as quantified by the suppression of the variance in e −βW , can at most reach that obtained from classical STA (within statistical error).…”
Section: Principle Of Minimal Work Fluctuations: Classical Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aspects of work fluctuations continue to be of fundamental interest [47][48][49][50]. Deep insights into work fluctuations are also relevant to designs of energy devices.…”
Section: Discussionmentioning
confidence: 99%